Neonchocotyle violantei n. sp. (Monogenea, Hexabothriidae) from Pseudobatos lentiginosus (Rhinopristiformes, Rhinobatidae) of Yucatán, Gulf of Mexico - Guadalupe Quiterio-Rendon; Scott Monks; Griselda Pulido-Flores (Revista Brasileira de Parasitologia Veterinária, 2018)
Abstract Neonchocotyle violantei n. sp. (Monogenea: Hexabothriidae) infects the gill of the Atlantic guitarfish, Pseudobatos lentiginosus (Rhinopristiformes, Rhinobatidae) from littoral waters of Celestún, Yucatán, Mexico. It is assigned to Neonchocotyle because it has, among other features, an asymmetrical haptor, a seminal receptacle, a smooth oötype, and an egg with two elongate filaments. It differs from Neonchocotyle pastinacae, the only congener, by having a small body (821 long by 315 wide, length to width = 2.6:1), two pairs of microhooks between the haptoral appendix suckers, extracaecal (submarginal) vaginal pores, and 5-9 testes. This is the first record of a species of Neonchocotyle in the Gulf of Mexico, the first monogenean reported from P. lentiginosus in Mexico and the second species of Hexabothriidae reported from Mexico.